Building Synergy: Collaborative Strategies and Effective Communication Between School Components to Build a Positive School Environment in the 21st Century Based on the Concept of Tri Hita Karana at SD Negeri 2 Banjar Tegal - Widiatmika, I Komang Adi; Oviantika, I Gede Krisna; Yoga, Kadek Sangging Semara; Wijaya, I Gede Dimas Rangga; Yadnya, I Ketut Wahyudi; Sukajay, I Gusti Ngurah Agung Susila; Werang, Basilius Redan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This article aims to build synergy through collaborative strategies and effective communication as an important step in creating a positive school environment at SD Negeri 2 Banjar Tegal based on Tri Hita Karana. By integrating the concept of Tri Hita Karana, it is expected that education can run harmoniously and sustainably, providing benefits for all parties involved. This research uses a descriptive qualitative approach with a case study design to examine collaborative strategies and effective communication between school components to build a positive school environment based on Tri Hita Karana. The results of this study confirm that building synergy through collaborative strategies and effective communication between school components is very important to create a positive learning environment. The application of the Tri Hita Karana concept can be a strong foundation in achieving goals by involving all parties in the educational process.